Sectoral Decomposition of Convergence in Labor Productivity : A Re-examination from a New Dataset - Dieppe, Alistair; Matsuoka, Hideaki (World Bank, Washington, DC, 2021)
This paper investigates how the sector-specific source or the changing sectoral composition of labor productivity has contributed to aggregate beta convergence, using a newly constructed eight-sector database. The main findings are twofold. First, both within and sectoral reallocation have become important drivers of aggregate convergence in labor productivity. Second, agricultural productivity growth has been a significant contributor to aggregate convergence, whereas catch-up in other sectors has only contributed a small amount to convergence. The strong growth of the agriculture sector has been the most important driver of aggregate productivity convergence even though agricultural productivity itself in low-income countries is weakly converging to that in advanced economies.